2020
DOI: 10.1088/2053-1591/ab7866
|View full text |Cite
|
Sign up to set email alerts
|

Pyrocatechol violet sensitized Ho-TiO2/ZnO nanostructured material: as photoanode for dye sensitized solar cells

Abstract: In this work TiO 2 , Holmium doped (Ho-TiO 2 ) Titanium oxide nanoparticles (NPs) and the corresponding nanostructured combinations (Ho-TiO 2 /ZnO NC) were successfully synthesized through sol gel method and reflux techniques respectively. The prepared nano materials were characterized with the help of x-ray diffraction Analysis (XRD), UV-visible spectroscopy, Scanning Electron Microscopy (SEM), Energy dispersive x-ray Analysis (EDX) and Fourier Transform infrared spectroscopy (FT-IR). The absorption spectra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“… where α denotes the absorption coefficient, h is the photon’s energy, A is the proportionality constant, and n is the electronic transition with 3% Ho/TiO 2 NPs n = 1/2; therefore, the calculated band gap is 2.77 eV. 29 , 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… where α denotes the absorption coefficient, h is the photon’s energy, A is the proportionality constant, and n is the electronic transition with 3% Ho/TiO 2 NPs n = 1/2; therefore, the calculated band gap is 2.77 eV. 29 , 30 …”
Section: Resultsmentioning
confidence: 99%
“…The aqueous suspension of the synthesized sample reveals an absorption peak at 311 nm, with a fundamental absorption edge at 520 nm. The energy gaps of holmium-doped TiO 2 were calculated by using a Tauc plot (Figure B). where α denotes the absorption coefficient, h is the photon’s energy, A is the proportionality constant, and n is the electronic transition with 3% Ho/TiO 2 NPs n = 1/2; therefore, the calculated band gap is 2.77 eV. , …”
Section: Resultsmentioning
confidence: 99%
“…The presence of Phenols, Flavonoids, Steroids, Glycosides, Alkaloids, Tannins, Plobatannins, Anthocynins, Leucoanthocynins, Couramins and Anthraquinones in the herbal extracts was evaluated by different phytochemical tests mentioned in table: Si-1 ( Roghini and Vijayalakshmi, 2018 ).The functional groups of the organic compounds were characterized by FT-IR spectroscopy (Bruker Platinum ATR) in the range of 4000 to 500 cm −1 in the selected plants extract ( Ullah et al, 2020a , Ullah et al, 2020b ). The proximate analysis of the respective plants was conducted using a spectrophotometer (Cecil CE-7400) with 2 mm width slit using 10 mm cell under UV–Vis light from 200 to 800 nm wavelength to calculate the band gap with the help of absorption spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Coccidiosis is economically important disease in poultry sector, causes US $ 3 billion loss annually ( Pawestri et al, 2020 , Quiroz-Castaneda and Dantan-Gonzalez, 2015 ) and almost US $ 0.8 billion is spent on prophylactic in-feed drugs ( Allen and Fetterer, 2002 ). In Pakistan, avian coccidiosis was not studied enough but institutional-based surveys revealed 32.79% prevalence on average in fecal and litter observation, the molecular study confirmed the presence of E. tenella, E. acervulina , E. necatrix, E maxima , E brunette, E. mitis and E. praecox ( Ayaz et al, 2003 , Khan et al, 2006 , Mustafa and Ali, 2005 , Abbas et al, 2015 , Sultana et al, 2009 , Bachaya et al, 2012 , Bachaya et al, 2015 , Awais et al, 2012 , Shamim et al, 2015 , Amin et al, 2014 , Rashid et al, 2019 , Ali et al, 2014 , Jamil et al, 2016 , Akram et al, 2018 , Naveed and Faryal, 2019 , Yousaf et al, 2018 , Sohail et al, 2019 , Khan, 2019 , Ullah et al, 2020a , Ullah et al, 2020b ). Eimeria spp are specific to different loci in the gastrointestinal tract of the avian host ( Lee and Lee, 2007 , Bachaya et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The catechol containing molecule boosted the efficiency of their device from 1.12% (for Ho–TiO 2 /ZnO) to 1.51% (for Ho–TiO 2 /ZnO/dye). [ 126 ] Adineh et al investigated DSSCs using dyes with catechol anchoring moiety and studied photogenerated electron injection mechanism in TiO 2 /catechol. They reported the high stability of catechol anchoring group on the TiO 2 surface and showed the DSSC fabricated using this catecholic dye have inconsiderable desorption of dye from the TiO 2 surface after days.…”
Section: Applicationsmentioning
confidence: 99%